2007
DOI: 10.1007/bf03030626
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin fromCurcuma zedoaria Rosc

Abstract: A mannose-binding lectin was isolated from rhizomes of the medicinal plant Curcuma zedoaria. We used extraction with 20 mM phosphate buffer, ammonium sulfate precipitation, ion exchange chromatography on Q-Sepharose, gel filtration chromatography on Superdex 75, and reverse-phase HPLC. The purified lectin yielded a single band on SDS-PAGE that corresponded to a molecular mass of 13 kDa. This lectin exhibited hemagglutinating activity toward rabbit erythrocytes, which could be inhibited by mannose only. The lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Note, however, that the predicted (theoretical) mass of the homologous proteins used to identify these three spots are slightly higher for A27 and A34 (19.5 and 20.3 kDa, respectively) but significantly so for A20 with a predicted mass of 404 kDa. A mannose binding lectin with a molecular mass of 13.4 kDa was also isolated from C. zedoary [ 39 ]. In addition, six homologous lectin proteins of various molecular masses (8.84-32.8 kDa) were found in C. aromatica [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Note, however, that the predicted (theoretical) mass of the homologous proteins used to identify these three spots are slightly higher for A27 and A34 (19.5 and 20.3 kDa, respectively) but significantly so for A20 with a predicted mass of 404 kDa. A mannose binding lectin with a molecular mass of 13.4 kDa was also isolated from C. zedoary [ 39 ]. In addition, six homologous lectin proteins of various molecular masses (8.84-32.8 kDa) were found in C. aromatica [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the widespread usage of members of this general for medical applications, reports of lectins from Curcuma plants are scarce. A mannose-binding lectin from the Zingiberaceae member, Curcuma zedoaria Rosc., has been identified and found to have sequence similarity to a mannose-binding lectin from the broad-leaved helleborine orchid, Epipactis helleborine (L) Crantz (Asparageles: Orchidaceae) [27]. In the related Curcuma aromatica, six putative proteins from nine bands derived from a rhizome preparation showed similarity with other lectin sequences [28], whilst a study on the hemagglutinating activity of Curcuma plants found hemagglutinating activity in the species of this study, Khamindum or Curcuma amarissima [29].…”
Section: Introductionmentioning
confidence: 94%
“…The purification process was slightly modified from the method described by Tipthara [24] in that Tris-HCl buffer pH 7.2 and an SP sepharose (Amersham Pharmacia Biotech, UK) column were used instead. Briefly, 100 mg of crude protein powder was dissolved in 10 ml of 20 mM Tris-HCl buffer pH 7.2.…”
Section: Extraction Of Protein From the Rhizomes Of Z Ottensiimentioning
confidence: 99%